The Use of Drill Method to Improve Elementary School Students’ Learning Outcomes in Vocabulary - Yusuf, Faidah; Usman, Hikmawati; Irfan, Muhammad (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2023)
This study employs a "quasi-experimental" design to determine whether there is an effect of using drill subjects English in elementary schools in Bajeng, Gowa Regency. The sample consisted of 14 students who were treated with the drill method in the experimental class. Purposive sampling was used in the sampling process. The observation results of the drill method implementation were classified as effective category at the first meeting and very effective category at the second meeting. As a result, the drill method's practical application has cultivated in this study. Therefore, it is possible to conclude that using the drill method has an effect on student learning outcomes in the English subjects at elementary schools.